The Challenge of Public Pension Reform in Advanced and Emerging Economies - Clements, Benedict; Coady, David; Eich, Frank; Gupta, Sanjeev (Washington, D.C. : International Monetary Fund, 2016)
Pension reform is high on the policy agenda of many advanced and emerging market economies. In advanced economies the challenge is generally to contain future increases in public pension spending as the population ages. In emerging market economies, the challenges are often different. Where pension coverage is extensive, the issues are similar to those in advanced economies. Where pension coverage is low, the key challenge will be to expand coverage in a fiscally sustainable manner. This volume examines the outlook for public pension spending over the coming decades and the options for reform in 52 advanced and emerging market economies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet